Bioavailability and nutrikinetics of rosemary tea phenolic compounds in humans. (January 2021) - Achour, Mariem; Bravo, Laura; Sarriá, Beatriz; Ben Fredj, Maha; Nouira, Manel; Mtiraoui, Ali; Saguem, Saad; Mateos, Raquel
Graphical abstract: Highlights: This is the first rosemary tea polyphenol (RTP) bioavailability study in humans. Forty-eight RTP metabolites were identified in plasma and urine. RTP are bioavailable and mostly metabolized by the colonic microbiota. Diydrocaffeic acid and its phase II derivatives was the major RTP metabolite group. Up to 22% of the ingested RTPs were recovered in urine. Abstract: Rosmarinus officinalis L. is a widespread aromatic plant commonly consumed as a tea in traditional cuisine and in folk medicine to treat various illnesses due to its therapeutic properties. To the best of our knowledge, there are no reports on the bioavailability and metabolism of R. officinalis tea polyphenols in humans. This study was aimed at assessing the bioavailability and nutrikinetics of R. officinalis phenolic compounds in healthy humans for the first time. Forty-eight compounds were identified in plasma and urine. Few un-metabolized compounds were detected since rosemary polyphenols were extensively metabolized into phase II conjugates, with rapid appearance and clearance in plasma, pointing to small intestinal absorption. Phase II derivatives of caffeic acid showed kinetics compatible with both intestinal and colonic hydrolysis of rosmarinic acid yielding free caffeic and 3, 4-dihydroxyphenyl-lactic acids, which were absorbed and metabolized into phase II derivatives. These metabolites, along with reduced forms of caffeic acid and their phase II metabolites, and those of hydroxyphenylpropionic, hydroxylphenylacetic, benzoic and hippuric acids, highlight the importance of colonic absorption. Total urinary excretion of the phenols added up to 235 µmol, corresponding to 22.3% of the ingested amount (1055 µM). In conclusion, rosemary tea polyphenols are partially bioavailable and extensively metabolized, mainly by the colonic microbiota.